Acute pancreatitis. A more common and severe complication of gallstones in males - Malik, Arshad M (International Journal of Health Sciences, 2015)
Objective: To describe an increased incidence and severity of gallstone pancreatitis in males compared to females. Design: Methods: This was a retrospective observational comparative study conducted at Liaquat University of Medical and Health Sciences, Jamshoro, Pakistan, over 3 years from June 2008 to June 2011. The study comprises two hundred and thirty seven (237) patients with a mean age of 52.38, Std 13.311,65 (22-87) with 157 (66.24%) females and 80 (33.75%) males who were admitted as acute abdominal pain secondary to gallstones were included in the study. The patients were mostly diagnosed on ultrasonography and enzyme studies. Demographics and other variables are studied and statistical analysis done on SPSS version 20. Results: More frequent cases of severe acute pancreatitis were observed in males with gallstones (70%) compared to females (P<0.001). The aged people had a high prevalence while males were more likely to develop local and systemic complications. Severity stratification was done based on different criteria’s like Ranson’s criteria, and APACHEII. Overall mortality was 7.59%. Mortality among males was significantly high (70%, n=16) in our study due to an increased incidence of fulminant course of the disease. Conclusion: Contrary to the belief, gallstone associated acute pancreatitis is getting more common in our society and especially so in male population. Key Words: Symptomatic gall stones, complications, male population, acute pancreatitis